2021
DOI: 10.1002/jev2.12177
|View full text |Cite
|
Sign up to set email alerts
|

A comprehensive study to delineate the role of an extracellular vesicle‐associated microRNA‐29a in chronic methamphetamine use disorder

Abstract: Extracellular vesicles (EVs), which express a repertoire of cargo molecules (cf. proteins, microRNA, lipids, etc.), have been garnering a prominent role in the modulation of several cellular processes. Here, using both non‐human primate and rodent model systems, we provide evidence that brain‐derived EV (BDE) miRNA, miR‐29a‐3p (mir‐29a), is significantly increased during chronic methamphetamine (MA) exposure. Further, miR‐29a levels show significant increase both with drug‐seeking and reinstatement in a rat MA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
27
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 24 publications
(30 citation statements)
references
References 148 publications
(193 reference statements)
0
27
0
Order By: Relevance
“…A previous study showed that HIV infection increases EV release in microglia [ 49 ]. We have previously demonstrated that meth increases EV releases in animal (rat and monkey brain tissues) and cell culture models [ 50 ]. However, the effects of meth on EV release in HIV infected cells have not been investigated.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…A previous study showed that HIV infection increases EV release in microglia [ 49 ]. We have previously demonstrated that meth increases EV releases in animal (rat and monkey brain tissues) and cell culture models [ 50 ]. However, the effects of meth on EV release in HIV infected cells have not been investigated.…”
Section: Resultsmentioning
confidence: 99%
“…Intriguingly, in uninfected U937 cells, meth did not increase the concentration of large 10 K particles when compared to the smaller 100 K particles ( Figure 1 B,C). In our recent study, we showed that meth increases EV biogenesis in uninfected microglial cells, however, it increased specifically smaller sized particles when compared to larger sized particles [ 50 ]. This could be the same in uninfected U937 cells as well.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Western blotting was performed as described in our previous studies [51,56,59]. Briefly, purified synaptosomes (7.5 µg) from each animal from the two groups were loaded onto 10% Bis-Tris wells (Invitrogen, Waltham, MA, USA) under reducing conditions, followed by transfer to a nitrocellulose membrane using iBlot2 (Invitrogen, Waltham, MA, USA) and immunodetection.…”
Section: Western Blotmentioning
confidence: 99%